Design, Synthesis, and Bioactivities of Novel Tryptophan Derivatives Containing 2,5-Diketopiperazine and Acyl Hydrazine Moieties - Lili Li; Rongxin Yang; Jianhua Liu; Jingjing Zhang; Hongjian Song; Yuxiu Liu; Qingmin Wang (Molecules, 2022)
Based on the scaffolds widely used in drug design, a series of novel tryptophan derivatives containing 2,5-diketopiperazine and acyl hydrazine moieties have been designed, synthesized, characterized, and evaluated for their biological activities. The bioassay results showed that the target compounds possessed moderate to good antiviral activities against tobacco mosaic virus (TMV), among which compounds 4, 9, 14, 19, and 24 showed higher inactivation, curative, and protection activities in vivo than that of ribavirin (39 ± 1, 37 ± 1, 39 ± 1 at 500 mg/L) and comparable to that of ningnanmycin (58 ± 1, 55 ± 1, 57 ± 1% at 500 mg/L). Thus, these compounds are a promising candidate for anti-TMV development. Most of these compounds showed broad-spectrum fungicidal activities against 13 kinds of phytopathogenic fungi and selective fungicidal activities against Alternaria solani, Phytophthora capsica, and Sclerotinia sclerotiorum. Additionally, some of these compounds exhibited larvicidal activities against Tetranychus cinnabarinus, Plutella xylostella, Culex pipiens pallens, Mythimna separata, Helicoverpa armigera, and Pyrausta nubilalis.